Addition of low dose acetazolamide as an adjunct in patients undergoing high dose methotrexate is safe and beneficial. Issue 3 (5th March 2020) - Ku, Matthew; Bazargan, Ali; Tam, Constantine
Abstract: Background: High‐dose methotrexate (HDMTx) is utilised in central nervous system lymphoma and acute lymphoblastic leukaemia due to its ability to penetrate the blood–brain barrier. Despite its efficacy, nephrotoxicity is a potentially serious toxicity that could also exacerbate other methotrexate‐related toxicities and compromise dose intensity. Acetazolamide (AZL) is a carbonic anhydrase inhibitor that causes an increase in bicarbonate excretion and consequently urine alkalinisation. Following occurrences of HDMTx‐induced acute kidney injury (AKI) due to inadequate urine alkalinisation at our institution, routine AZL was administered to appropriate patients from 2010 onwards. Aims: To analyse the addition of AZL to routine renoprotective measures, given that inadequate urinary alkalinisation is the major risk factor for methotrexate crystal precipitation and prolonged excretion. In addition, since fluid overload is a common consequence of HDMTx treatment, the effect of AZL on fluid balance was also examined. Methods: This is a retrospective, single‐centred cohort study examining the mitigation of HDMTx‐induced toxicities by AZL in 92 patients over a 6‐year period. Results: AZL showed a strong trend of preventing either AKI (as per CTCAE version 4.03) or delayed methotrexate elimination (>5 days), especially in males. Furthermore, AZL also resulted in reduced weight gain and fewer episodes of urinary pH <7.0. Conclusion: AZL appeared to diminish the incidence of HDMTx‐induced toxicities, including reducing oedema‐related weight gain. With mild, preventable hypokalaemia as the only noteworthy toxicity, AZL could be considered as an adjunct to HDMTx patient care.